Pseudo Three-Component Synthesis of 1,3-Dioxol Derivatives from the Reaction Between Isocyanides and Aldehydes in Solventless Conditions - Reza Kazemizadeh, Ali; Ramazani, Ali (Asian Journal of Chemistry, 2012)
Pseudo three-component reaction between isocyanides and aldehydes in a 1:2 ratio in solventless conditions at room temperature led to 1,3-dioxol derivatives in high yields. The reaction proceeds cleanly under mild conditions and no side reactions were observed. The structures of the products were deduced from their 1H NMR, 13C NMR, mass, IR spectra and elemental analysis.